Aldehyde-induced DNA-protein crosslinks- DNA damage, repair and mutagenesis - Blouin, Thomas; Saini, Natalie (Frontiers in Oncology, 2024)
Aldehyde exposure has been shown to lead to the formation of DNA damage comprising of DNA-protein crosslinks (DPCs), base adducts and interstrand or intrastrand crosslinks. DPCs have recently drawn more attention because of recent advances in detection and quantification of these adducts. DPCs are highly deleterious to genome stability and have been shown to block replication forks, leading to wide-spread mutagenesis. Cellular mechanisms to prevent DPC-induced damage include excision repair pathways, homologous recombination, and specialized proteases involved in cleaving the covalently bound proteins from DNA. These pathways were first discovered in formaldehyde-treated cells, however, since then, various other aldehydes have been shown to induce formation of DPCs in cells. Defects in DPC repair or aldehyde clearance mechanisms lead to various diseases including Ruijs-Aalfs syndrome and AMeD syndrome in humans. Here, we discuss recent developments in understanding how aldehydes form DPCs, how they are repaired, and the consequences of defects in these repair pathways.